2016
DOI: 10.4103/0974-2700.179461
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic injuries in patients with diabetes mellitus

Abstract: Diabetes mellitus (DM) is associated with increased in-hospital morbidity and mortality in patients sustained traumatic injuries. Identification of risk factors of traumatic injuries that lead to hospital admissions and death in DM patients is crucial to set effective preventive strategies. We aimed to conduct a traditional narrative literature review to describe the role of hypoglycemia as a risk factor of driving and fall-related traumatic injuries. DM poses significant burden as a risk factor and predictor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 73 publications
(133 reference statements)
1
12
0
Order By: Relevance
“…Men commute by car more often than women. Hypoglycaemia and other complications related to advanced diabetes can cause a deterioration in driving performance as a result of compromised psychomotor skills, poorer visuo-spatial functions, slower information-processing, decreased vigilance and poorer judgement [24]. Our finding is consistent with that of a previous study which reported the risk of motor vehicle crash-related injury to be almost twice as high in drivers with Type 1 diabetes as in drivers who do not have diabetes [25].…”
Section: Discussionsupporting
confidence: 91%
“…Men commute by car more often than women. Hypoglycaemia and other complications related to advanced diabetes can cause a deterioration in driving performance as a result of compromised psychomotor skills, poorer visuo-spatial functions, slower information-processing, decreased vigilance and poorer judgement [24]. Our finding is consistent with that of a previous study which reported the risk of motor vehicle crash-related injury to be almost twice as high in drivers with Type 1 diabetes as in drivers who do not have diabetes [25].…”
Section: Discussionsupporting
confidence: 91%
“…There is a dire need of behavior change communication in healthcare experts, public education, law enforcement, newer technology, and special care for elderly population. [44] Parkinson's disease may lead to unsafe driving with variable impairments in vision and cognition. [45] Routine changes due to senility like diminished eyesight and slow reaction time should not be equated with Alzheimer's disease.…”
Section: Risk Factors For Road Traffic Accidentsmentioning
confidence: 99%
“…[2,5] In those with traumatic injuries diabetes has been reported as both a risk factor and predictor of worse outcomes. [6] A number of studies conclude that those with type 2 diabetes have a higher risk of fracture than those without diabetes although risk estimates vary considerably from 20% higher to three-fold depending on the inclusion criteria (e.g. type of diabetes, age of patients), skeletal site, diabetes duration and study design.…”
Section: Introductionmentioning
confidence: 99%